Dynamics of Exchange in the Beaufort Sea Boundary Current System: Implications for Interior Ventilation - Pickart, Robert S (2006)
The long-term goal is to understand more clearly the dynamics of high-latitude shelfbreak jets in the presence of strong forcing. This includes the response to external forcing (e.g. winds, air-sea buoyancy flux) and internal forcing (e.g. baroclinic instability).